Becoming the Phenomenon? An Alternative Approach to Reflexivity in Ethnography. (November 2016) - Müller, Sophie Merit
This article presents a praxeologically informed approach to "transgressing the researcher-subject" in ethnography. I unfurl a concept of "strong" reflexivity as developing a perspective of unfamiliarity toward one's own practices and beliefs. By drawing on my study on practicing ballet, I illustrate how I dealt with my own bodily involvement as a professional dance student. Comparing my approach with evocative autoethnography, I not only emphasize that corporeal sensitivity and alertness are inherent to both styles of inquiry. Yet, I also point out their differences. Whereas evocative autoethnography takes subjectivity as a resource for insights, this approach uses it as an instrument for discovery.